Legal Protection of Journalists' Rights Based on Law No 40 of 1999 on Freedom of the Press - Albertus Makur; Ernu Widodo; Mahon Nitin (Yayasan Adra Karima Hubbi, 2023)
This thesis is entitled legal protection for the journalist profession by raising several issues including the following: (a) abuse or physical violence against journalists who are carrying out their duties, (b) deletion, falsification of news reports produced by journalists, (c) intimidation or pressure on journalists to stop or limit the delivery of news or reports relating to the public interest, (d) prohibiting access or blocking journalists from gathering information or covering an event. Based on the main points calculated in the background, the researcher can analyze it to determine the formulation of the problem as follows what are the forms of criminalization of journalists' rights of profession and the legal protection of the rights of journalists who are criminalized by other parties. The research methods as researchers in a scientific or scientific way to get a discussion of theoretical studies. This research method consists of: (1) The type of research method used in this writing is the normative legal research method. (2) descriptive approach (3) and sources of legal materials consisting of secondary, primary and tertiary sources of legal materials, then also processing of legal materials and analysis of legal materials. Then the literature review section consists of (1) an overview of previous research, (2) an overview of journalists and the press, (3) an overview of legal protection, (4) an overview of victims. This literature review serves as a theoretical basis in outline so that it can complete the discussion and theory sections which consist of: (1) Forms of criminalization of the rights of the journalist profession, (2) Legal protection of the journalist profession which is criminalized by other parties.